IL‐17 in neonatal health and disease. (15th December 2017) - Lawrence, Shelley M.; Ruoss, Jessica Lauren; Wynn, James L.
Abstract : Over the last few years, scientific interest in the cytokine IL‐17A has intensified as its role in human health and disease has been elucidated. Discovered almost a quarter century ago, IL‐17A is known to have poor biologic activity when acting alone, but attains robust actions when working synergistically with potent mediators of proinflammatory immune responses, such as IL‐6 and IL‐8. IL‐17A is produced by specialized innate immune cells that protect host barriers from the outside world. Like sentries, these innate immune cells can "sound the alarm" through increased production of IL‐17A, causing activation and recruitment of primed neutrophils and monocytes when pathogens escape initial host defenses. In this way, IL‐17A promulgates mechanisms responsible for pathogen death and clearance. However, when IL‐17A pathways are triggered during fetal development, due to chorioamnionitis or in utero inflammatory conditions, IL‐17A can instigate and/or exacerbate fetal inflammatory responses that increase neonatal morbidities and mortality associated with common neonatal conditions such as sepsis, bronchopulmonary dysplasia (BPD), patent ductus arteriosus (PDA), and necrotizing enterocolitis (NEC). This review details the ontogeny of IL‐17A in the fetus and newborn, discusses how derangements in its production can lead to pathology, and describes known and evolving therapies that may attenuate IL‐17A–mediated human conditions.